Prevalence of Italian children living in food insecure households and their health status. (13th November 2019) - Zace, D; de Waure, C; Teleman, A; Reali, L; Di Pietro, M L
Abstract: Background: Food insecurity poses a major threat to population's health status. Children, if affected, are particularly vulnerable to the possible sequels of food insecurity. Considering that, we aimed to assess the prevalence of children (born in Italy, from Italian parents) living in food insecure households and the association with their health and socio-economic conditions. Methods: The study was conducted from January 2017 to December 2018 in pediatric offices. Parents answered to the 18-items of the Household Food Security Index, 8 of which specifically concern children. Households were classified in 4 categories: very low, low, marginal and high food security, creating then a dichotomized variable (food secure and insecure). Pediatricians answered a dedicated questionnaire on children's health status. We used logistic regression to assess the socio-economic variables predicting food insecurity and chi2 test to evaluate the association between food insecurity and children's health status. Results: Based on parents' answers, among 573 households with children, 15.4% were food insecure. Food insecurity was associated to lower parent's education and employment, worse household's economic condition, higher number of children within a family and geographic location (living in south Italy rather than north). There was a significant association between food insecurity and the presence of visual, relational, psychomotor, dental and physical impairments in children. Conclusions: Almost 1 Italian child in 7 lives in food insecure households. Children living in food insecure households have higher probability of having physical, mental and social health problems. Considering the impact on children's health, food insecurity emerges as a public health issue and should be addressed through the appropriate measures. Key messages: Food insecurity among children represents a public health issue even in a developed country such as Italy, affecting children's present and future health. Policy makers should consider screening children for food insecurity and taking appropriate actions, especially for the at-risk population.